Ultrasonic investigations of 2.ethylhexadiole-1.3. In the region of viscoelastic relaxation - Marek WACIŃSKI; Ryszard PŁOWIEC (Archives of Acoustics, 2016)
This paper gives the results of measurements of mechanical shear impedance in 2-ethylhexadiole-1.3., at frequencies of 0.520, 29.9 and 500 MHz. Measurements carried out with transverse waves in the region of viscoelastic relaxation permitted the determination of viscoelastic relaxation times and the characteristic constant quantities such as the modulus of elasticity, mechanical compliance and dynamic viscosity.